Protein fibrillation: the good, the bad and the ugly (2020)
Protein fibrillation is a process in which the peptide chains are slightly modified form native structure to yield fibers. The mechanism that leads to this fiber conformations is little known. An accepted hypothesis is the “entropic cone”, according to this hypothesis a pre-unfolded structure plays a crucial role in the fiber growth. Fibrillation can offer certain advantages, since the new structure offers technological possibilities. On the other hand, when the process occurs inside tissues could be responsible to generate a series of illness known as “amyloidosis”. At the University Antonio Nariño a family of macrocyclic molecules, the resorcinarenes, is been studied. Preliminary results indicate that thismacrocycles are able to inhibit the fibrillation of certain proteins.